Prepositions in MSA and English - Aldwayan, Saad Nasser (Linguistik Online, 2014)
Spatial scenes are identical in the world languages. However, cultures may diverge in profiling spatial scenes (Levinson 2003). This paper selects for study the prepositions in and on in English and their Modern Standard Arabic (MSA) counterparts fi and 3ala, arguing that MSA and English seem to diverge in the spatial configurations and meanings of these prepositions. The sub-schemas of CONTAINMENT (in-ness) in MSA are found to partially overlap with those of English, with the other sub-schemas being taken care of by SUPPORT (on-ness) and PUNCTUALITY (point-ness). Such differences classify MSA more as a CONTAINMENT-based language than English, which seems to prefer SUPPORT and PUNCTUALITY. However, English and MSA seem to converge in their metaphoric conceptualizations of states owing to conceptual embodiment (Lakoff 1987). The article discusses the implications of such findings for spatial cognition and cultural cognition and EFL/ESL writing and translating.